Visions of power. Comments on the relationship between space, law and light - Bertolotti, Riccardo (E|C, 2020)
Assuming that the shape of the spaces is related to the kind of the juridical culture expressed within a society, we suggest that such a relationship may emerge in institutional places better than in other sites. But law is also a specific kind of knowledge, which manifest by putting itself on the scene, in order to be seen and get crossed. Therefore, in this paper we propose to consider the cognitive dimension as mediated by the “matter” of light. Two case-studies of institutional places located in Roma are shortly compared in the following: the italian parliamentary aula (Montecitorio) and the piazza del Campidoglio.